Vietnamese Young Consumer’s Attitude Towards Purchasing Organically Produced Food - Pho, Thi Tuong Vy (2020)
In the recent years, the Vietnamese organic market has grown dramatically. This is due to Vietnamese consumers are switching over and more prefer to organic food products, which follows the new trend of lifestyle by having the optimal healthcare and body care.